Preservation of microbiological and sensory quality of sheep meat using pomegranate bark extracts - Elfazazi K.; Chafki L.; Benbati M.; Fakhour S.; Haddioui A.; Elhansali M. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Fresh meat is a sensitive and unstable product over time due to its composition and physicochemical characteristics (pH and aw). The length of storage time depends on temperature, atmospheric oxygen, endogenous enzymes, humidity, light and, above all, the microorganisms initially present. The challenge of preserving meat dates back to antiquity and has now intensified with the industrialization of meat products. Thus, in this work, we studied the conservation of meat by pomegranate bark extract to extend meat storage time, which may be a promising way to promote this coproduct of pomegranate in meat industry. We evaluated the effect of pomegranate bark extract on the growth of microorganisms naturally present in sheep meat. We carried out the microbial germ count by the decimal dilution method. We performed successive dilutions of the sample in sterile physiological water. Then, we evaluated total aerobic mesophilic flora (TAMF) and total coliforms (TC) The treated meat with three concentration of extracts (50-25-0.12 mg /ml) were stored at 4°C. Then, we monitored the physicochemical and microbiological modification during 12 days of conservation. The results show that the microbial kinetics of the strains were significantly affected by pomegranate bark extract especially with high concentration (C1 = 50 mg/ml). A significant increase in UFC (colony-forming unit) over time was observed in the untreated meat. In conclusion, pomegranate bark extract has a preservative effect against microbial alteration of raw sheep meat.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)